The True Love of a Princess as Seen in William Shakespeare’s King Lear - Helmita Helmita; Lina Marlina (Fakultas Sastra Universitas Ekasakti, 2018)
This research is a study of psychological approaches that discuss the external aspect of drama King Lear by William Shakespeare. In this study the writer will discuss some of the problems that is (1) What does the king Lear prove his unconditional love to his youngest daughter (2) How does the King Lear’s youngest daughter prove her unconditional love to her father (king Lear) (3) How does the king Lear face the death of his youngest daughter. The purpose of this study is (1) To describe the king Lear prove his unconditional love to his youngest daughter (2) To describe the youngest daughter of king Lear prove unconditional love to his father king Lear (3) To explain the king Lear face the death of his youngest daughter. The theory used in this research is the theory of literary psychology according to Sigmund Freud and Carl rogers. This study used a qualitative method .The object of the study is William Shakespeare's William Lords drama. The data source is divided into two primary data sources and secondary data sources. The primary data source is the drama script itself. The secondary data source is the text of the text and some references related to the research. Data collection techniques are noted. Data analysis technique is descriptive analysis.The results show the following conclusions. First, the true love of a father to his daughter. Second, the true love of a daughter to her father. Third, when a father regrets his past decisions that can not see his daughter's love from the heart and must accept her daughter's gone ever.